(untitled) (Historia, 2021)
Reading Butterflies and Barbarians proved to be a slow, but very satisfying experience, mainly, I would say, on account of the creation-of-knowledge theme, of the intricacy of the data, and of the depth and quality of the argumentation. Being a keen reader of early archaeological and anthropological literature, I find the subject matter of the study fascinating. In the following pages, I will examine Chapter 8, which provides the conclusion of the epistemological analysis, for which the preceding chapters have paved the way.